Airborne Cyanobacterial Toxins and Their Links to Neurodegenerative Diseases - Zachary James Morris; Elijah W. Stommel; James Spencer Metcalf (Molecules)
Cyanobacteria can produce a wide range of toxins which have acute and chronic adverse health effects. Affecting a variety of mammalian systems, they are generally characterized according to their mode of action and the organs affected. Cyanobacterial neurotoxins are one cyanotoxin class that can negatively affect human health, and representatives of other cyanotoxins classes are increasingly showing neurotoxic effects. Of the various human exposure routes to cyanobacterial toxins, the significance of the airborne and inhalation route requires much greater clarity and understanding. People may be exposed to mixtures of cyanobacterial neurotoxins through the inhalation of sprays and dust, along with the potential to directly enter the central nervous system when crossing the blood-brain barrier. This review aims to summarize the current state of knowledge concerning airborne cyanobacterial neurotoxins, research gaps, health effects, and the need for management practices to protect human and animal health.